BUILDING DESIGN OF SOCIAL SECURITY SYSTEM AND SOCIAL JUSTNESS IN ISLAMIC ECONOMIC PRINCIPLE (International Conference on Social and Islamic Studies, 2022)
This is article purpose to explaining about social security system and social justness in islamic economic perspection. By using review literature. This article explaining islamic social security. This article to conclution so that design of social security system. Below 1. Security of individual; 2. Personality an a family security; 3. Personality and society; 4. Society in this coutry. Therefore, contruction of social security system in Islamic economic to explain so that the security are many kinds if social securty can achieve by individual, therefor enough at individu level. If it can’t achieved in individu level, can do it in family level. If can’t do it in family level can do it in society level. If can’t do it in society level to become duty of goverment in our country to do it.